2020
DOI: 10.1002/agg2.20092
|View full text |Cite
|
Sign up to set email alerts
|

Soybean profitability and yield component response to nitrogen fertilizer in Iowa

Abstract: Nitrogen fertilizer application to soybean [Glycine max (L.) Merr.] in Iowa, USA, has shown inconsistent results. We performed a study in central Iowa (2015 and 2016) to investigate the effect of N fertilizer rate (0, 45, 90, 135 kg N ha −1) and application timing (planting, flowering, pod setting) on soybean yield, yield components, and to calculate the economic net return to N fertilizer. Results showed a positive effect of N fertilizer on soybean yield and yield components both years. Seed and aboveground b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…5a). This may be partly due to the fact that LPJ-GUESS at this point does not model soybean hulls, which account for~15-20% of the total above-ground dry matter at harvest in the U.S. soybean rain-fed cropping system (Córdova et al, 2020). The observed increase in shoot and leaf biomass due to water supply was 19% and 21%, respectively.…”
Section: Response To Irrigationmentioning
confidence: 96%
See 2 more Smart Citations
“…5a). This may be partly due to the fact that LPJ-GUESS at this point does not model soybean hulls, which account for~15-20% of the total above-ground dry matter at harvest in the U.S. soybean rain-fed cropping system (Córdova et al, 2020). The observed increase in shoot and leaf biomass due to water supply was 19% and 21%, respectively.…”
Section: Response To Irrigationmentioning
confidence: 96%
“…In addition, due to the difficulties in measuring both nodules and roots in the field directly, in many studies the observed BNF rates were determined from plant above-ground biomass. Excluding the root contribution to the whole plant BNF rates most likely result in an underestimation of N fixation (Córdova et al, 2019(Córdova et al, , 2020: N associated with nodules and roots in soybean and faba bean may account for 20-40% of the total N accumulation at mid-flowering phase (Unkovich and Pate, 2000;Khan et al, 2003).…”
Section: N Fixation and %Ndfamentioning
confidence: 99%
See 1 more Smart Citation
“…5a). This may be partially due to the fact that LPJ-GUESS at this point does not model soybean hulls, which account for ∼ 15 %-20 % of the total aboveground dry matter at harvest in the US soybean rain-fed cropping system (Córdova et al, 2020). The ob-served increase in shoot and leaf biomass due to water supply was 19 % and 21 %, respectively.…”
Section: Response To Irrigationmentioning
confidence: 98%
“…For example, in the CROPGRO model (Boote et al, 2008), N fixation in soybean starts in the second trifoliolate stage and continues until the end of physiological maturity, whereas it ceases at the middle of the seed-filling period in the EPIC model (Cabelguenne et al, 1999). Much experimental evidence has indicated that the N fixed by legumes varies widely among crop growth stages, with the largest BNF rate observed between the late vegetative phase and the early seed-filling period (Santachiara et al, 2017;Córdova et al, 2020;Ciampitti et al, 2021). In this study, a specific function, similar to the temperature response function, is thus implemented in the BNF scheme to represent the variation of N fixation with the course of the legume life cycle:…”
Section: Representation Of Bnfmentioning
confidence: 99%